Detection of 16S Mitochondrial Gene Polymorphism on Barb Fish (Barbodes binotatus Valenciennes, 1842) from Lake Lebo Taliwang, West Nusa Tenggara - Tuty Arisuryanti; Astin Alfianti; Nadya Ulfa Nida' Firdaus; Lukman Hakim (Universitas Gadjah Mada, 2020)
The spotted barb fish (Barbodes binotatus), a tropical cyprinid fish, is one of the abundant fishes in Lake Lebo Taliwang commonly consumed due to high nutrition and utilized as an aquarium trade due to their exotic colour. However, no genetic information related to the intra-population genetic variation of the fish species in Lake Lebo Taliwang. Genetic information of the spotted barb fish can play an important role for the fish conservation. Therefore, the objective of this study was to detect 16S mitochondrial gene polymorphism of the spotted barb fish which can be used to detect their genetic variation. The method used in this study was a PCR method with primers 16Sar and 16Sbr. The data was then analysed using MESQUITE, MEGA, DnaSP and PopART to identify 16S mitochondrial gene polymorphism. This study obtained 610 base pairs after alignment of 16S sequences of all samples. Five haplotypes were detected with 9 variable sites and 2 parsimony informative sites. Haplotype diversity and nucleotide diversity of the spotted barb fish were 1.00 and 0.0066 respectively. In addition, genetic distance among the samples was 0.66. This finding exhibited polymorphism on 16S gene sequence among the fish samples and this data indicated genetic variation of the spotted barb from Lake Lebo Taliwang.